Effects of work-family conflict, work-family balance and support on well-being of private university academicians - Rahman, Mohammad Mizanur (2019)
Work and family are the two most important domains of employees’ lives. Work- Family Conflict (W-FC), Work Family Balance (WFB), Work Family Support (WFS) and Well-being (job, family and life satisfactions) are very crucial to academicians because of experiencing blurred boundary between work and family domains. W-FC is defined as a form of inter-role conflict in which role pressures from the work and family domains are mutually incompatible in some aspects. Considering the assumptions of work family boundary theory, the present study distinguishes the directionality of the W-FC that is work interferences with family is known as Work to Family Conflict (W to FC) which is viewed as a distinct construct from family interferences with work is called Family to Work Conflict (F to WC). Apart from the work family border theory, the Conservation of Resources (COR) theory, has been used to select two variables named WFB and WFS to develop a research model for the study. In order to determine the effects of work-family conflict on well-being; the present study has been segregated into three identifiable parts which are (a) to determine the direct effects of work to family conflict, family to work conflict on wellbeing (b) to examine whether work family balance mediates the relationship between work to family conflict, family to work conflict and well-being (c) to test the moderating effect of WFS in the relationship between work to family conflict, family to work conflict and well-being. Convenience sampling technique has been adopted to select the sample size while a cross-sectional survey research design method and a selfadministered survey questionnaire have been used to collect the data from 386 academicians who work in the private universities in Bangladesh. In this study, the Structural Equation Modeling (SEM) using AMOS and SPSS software are adopted as statistical data analysis tools. Confirmatory Factor Analysis (CFA) was used to determine the fit indices of the structural model which shows the direct effects of work to family conflict, family to work conflict on well-being. Meanwhile, bootstrapping mediation and multi-group analyses using SEM have been used to test the mediation and moderation effects. The findings of the current study based on the output of the structural model discovered that both directions of work-family conflict have significant negative effect on well-being. However, test of mediation using bootstrapping confirmed that WFB mediates only the relationship between work to family conflict and well-being but not the relationship between family to work conflict and well-being. These findings partially support Conservation of Resources (COR) theory. Finally, the output of multi-group analysis for moderation revealed that WFS does not moderate the relationship between both directions of work-family conflict and well-being. In addition to the theoretical implications, the results of this study suggest that work to family conflict, family to work conflict are negatively related to wellbeing among the academicians of private universities in Bangladesh. Therefore, higher authorities of private universities should pay more attention to work-family conflict issues because of their detrimental effects on well-being.